Femtosecond mode-locked erbium-doped fiber laser based on MoS2–PVA saturable absorber - Ahmed, M.H.M.; Latiff, A.A.; Arof, Hamzah; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2016)
We fabricate a free-standing few-layer molybdenum disulfide (MoS2)–polymer composite by liquid phase exfoliation of chemically pristine MoS2 crystals and use this to demonstrate a soliton mode-locked Erbium-doped fiber laser (EDFL). A stable self-started mode-locked soliton pulse is generated by fine-tuning the rotation of the polarization controller at a low threshold pump power of 25 mW. Its solitonic behavior is verified by the presence of Kelly sidebands in the output spectrum. The central wavelength, pulse width, and repetition rate of the laser are 1573.7 nm, 630 fs, and 27.1 MHz, respectively. The maximum pulse energy is 0.141 nJ with peak power of 210 W at pump power of 170 mW. This result contributes to the growing body of work studying the nonlinear optical properties of transition metal dichalcogenides that present new opportunities for ultrafast photonic applications.